Picture Series Strategy and Motivation in Eleventh Grade Speaking Achievement: An Experimental Research Design - Syaputra, Tomi; Budiyanto, Darmawan; Tridinanti, Gaya; Ridho, M. Rasyid (CV. Doki Course and Training, 2023)
Despite the fact that speaking proficiency is essential for learning a foreign language, the majority of students struggle with it. This research set intended to discover: (1) whether or not students who trained to use the picture sequence approach and those who studied the presenting strategy had significantly different speaking abilities, (2) whether or not there was motivated and uninspired students perform significantly differently in speaking tasks, (3) whether or not there was the interact of picture series and motivation on speaking achievement. There were 60 students as sample and used purposive sampling, quantitative with factorial design approach, the information was gathered utilizing a speaking test and a questionnaire, paired sample t-test, independent sample t-test, and two-way ANOVA. Results, there is a big gap in speaking ability. It was proved by the result of paired t-test with t obtained (-13.950) was lower than t- table (1.697) and the significant value (0.000) was lower than a (0.05). It indicated that students' speaking achievement was improved. Also, it was proved by the result of independent sample t-test with t obtained (4,516) was higher than t- table (1.697) and the significant value (0.000) was lower than a (0.05). It indicated that students' speaking achievement was improved. In addition, the result of two-way ANOVA showed that A significant value was obtained of 0.003 < 0.05, that there was a difference between experimental group and the control group's speaking proficiency among students was motivated and uninspired. A significant value was obtained of 0.010 <0.05, Consequently, it could be said that there was a difference in speaking achievement between students who were motivated and those who weren't. A significant value of 0.355 > 0.05 was obtained, so it could be concluded there was no interact between learning methods and student motivation towards speaking achievement.